Assessment of the environmental and social value of Lake Doirani - Stergiou A.; Damigos D.; Karatassiou M. (Pastoralism and sustainable development: proceedings, 2021)
Doirani is a cross-border lake between Greece and the Former Yugoslav Republic of Macedonia and belongs in Kilkis. The importance of this wetland has led to its protection by European and National Legislation. In recent years, the water balance of the lake has been disturbed and has led to the decline of the fauna and the avifauna. Regarding the aesthetic value of the lake, on the Skopje side there is a great interest in the condition and protection of the lake in contrast to the Greek side where there is indifference, dirt and stench. The goal of the research was to record the views of the respondents regarding the current state of the lake and whether they consider that they benefit from it. The implementation of the research started from the construction of the respective questionnaire. The sample size was selected at 339 units (inhabitants), while the method followed was that of random sampling, at random locations in the study area. The results showed that most respondents believe that Doirani is in a miserable stateand that their quality of life and financial situation is significantly affected by it.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)